ORGANIZATION OF PROMOTION OF TRANSPORT AND LOGISTICS SERVICES TO TARGET MARKETS - Klymenko , V.V.; Novalska , N.I.; Lozova , G.M. (The actual problems of regional economy development, 2022)
The article is devoted to the analysis of the promotion of transport and logistics services to target markets and the assessment of the competitiveness of transport and logistics companies. The aim of the article is to analyze the nature and features of the process of promoting transport and logistics services to target markets, identify current trends in the organization of this process taking into account the requirements of domestic and international markets and substantiate the model of competitiveness of transport and logistics company assessment. In the process of research, the authors used the dialectical method, which revealed the economic nature of transport and logistics services, revealed the basic conditions for the functioning of the transport and logistics services market. Systemic and synergetic approaches allowed to formulate the author's method of calculating the integration indicator for assessing the competitiveness of the transport and logistics company. Due to the analysis of the target market for different components of the activities of transport and logistics companies, the market segmentation of transport and logistics services was carried out according to different criteria, including the market strategy used in the market. The authors identified how each factor affects the level of competition in the market and revealed the main types of competitive behavior of transport and logistics companies (including transportation of customer cargo on a certain route at the same price but different time; transportation of goods on a certain route with the same speed). It is noted that the market of transport and logistics services due to the specifics of the organization of production and provision of services is characterized by a high degree of differentiation, dynamism of market processes, sensitivity to changes in market conditions, territorial segmentation. The optimal combination of elements of marketing communications for a modern transport and logistics company was determined. The methodology of the analysis of the target market and the model for the assessment of competitiveness of the transport and logistic enterprise, offered by authors, represents scientific interest. The authors represented in practice the method of calculating the integration indicator for assessing the competitiveness of the transport and logistics company in the form of a mathematical model that takes into account the specifics of the transport industry in the European integration process.